Duck Tembusu Virus Infection Promotes the Expression of Duck Interferon-Induced Protein 35 to Counteract RIG-I Antiviral Signaling in Duck Embryo Fibroblasts - Zhou, Peng; Ma, Lei; Rao, Zaixiao; Li, Yaqian; Zheng, Huijun; He, Qigai; Luo, Rui (Frontiers in Immunology, 2021)
Duck Tembusu virus (DTMUV) is an emerging pathogenic flavivirus that has caused a substantial drop in egg production and severe neurological disorders in domestic waterfowl. Several studies have revealed that viral proteins encoded by DTMUV antagonize host IFN-mediated antiviral responses to facilitate virus replication. However, the role of host gene expression regulated by DTMUV in innate immune response remains largely unknown. Here, we utilized a stable isotope labeling with amino acids in cell culture (SILAC)-based proteomics analysis of DTMUV-infected duck embryo fibroblasts (DEFs) to comprehensively investigate host proteins involved in DTMUV replication and innate immune response. A total of 250 differentially expressed proteins were identified from 2697 quantified cellular proteins, among which duck interferon-induced protein 35 (duIFI35) was dramatically up-regulated due to DTMUV infection in DEFs. Next, we demonstrated that duIFI35 expression promoted DTMUV replication and impaired Sendai virus-induced IFN-β production. Moreover, duIFI35 was able to impede duck RIG-I (duRIG-I)-induced IFN-β promoter activity, rather than IFN-β transcription mediated by MDA5, MAVS, TBK1, IKKε, and IRF7. Importantly, we found that because of the specific interaction with duIFI35, the capacity of duRIG-I to recognize double-stranded RNA was significantly impaired, resulting in the decline of duRIG-I-induced IFN-β production. Taken together, our data revealed that duIFI35 expression stimulated by DTMUV infection disrupted duRIG-I-mediated host antiviral response, elucidating a distinct function of duIFI35 from human IFI35, by which DTMUV escapes host innate immune response, and providing information for the design of antiviral drug.